Challenges of SOA adoption in the Telco domain for Latin American researchers - Mendioroz-Cotelo, Fernando; Rendón-Gallón, Álvaro; Corrales-Muñoz, Juan Carlos; Rojas-Meléndez, Julián Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Telecommunication service providers such as Mobile Network Operators are currently under the vortex arising from paradigm shifts imposed by the omnipresence of the Internet. The adoption of Service Oriented Architecture and the shift to Next Generation Networks constitute some of the efforts of these organizations at the confluence toward these new business models. This article introduces a review of the concepts behind these proposals within Telco organizations, identifies gaps and discusses about the challenges that research and development groups are facing in the Latin American context, obstacles to overcome for converging and creating a synergic environment of common interests oriented to the innovation around the subject.